2018
DOI: 10.1016/j.bjm.2018.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Salmonella spp. in cattle egrets ( Bubulcus ibis ) from Fernando de Noronha Archipelago, Brazil

Abstract: The growth of the population of cattle egrets (Bubulcus ibis) in the archipelago of Fernando de Noronha constitutes a threat to public health and biological diversity because of their competition with and predation on native species and the possibility of transmission of pathogens to human beings, livestock and native wildlife. The aim here was to search for, isolate and identify serovars of Salmonella in clinically healthy local cattle egrets. Cloacal swabs were obtained from 456 clinically healthy cattle egr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Considering the landscape and that tegus in FN have a home range of up to 15 hectares [ 18 ], the detection of the same genotype in distant capture areas at the same sampling season suggests other species could be involved in Salmonella dissemination throughout the island. Humans, birds [ 39 , 40 ] or domestic animals could be involved on this transmission chain, but further studies are required to stablish the complete Salmonella dynamics in FN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the landscape and that tegus in FN have a home range of up to 15 hectares [ 18 ], the detection of the same genotype in distant capture areas at the same sampling season suggests other species could be involved in Salmonella dissemination throughout the island. Humans, birds [ 39 , 40 ] or domestic animals could be involved on this transmission chain, but further studies are required to stablish the complete Salmonella dynamics in FN.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the serotypes detected in wild tegus had already been reported in reptiles worldwide, of which Agona, Braenderup, Panama, Rubislaw, Saintpaul, and Worthington serotypes had been previously detected in Brazilian captive tegus [ 6 , 35 ]. As previously stated, most of these serotypes have also been identified in humans, birds (including poultry), pigs, and cattle [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in methods of microorganism detection have shown that wild animals often are natural reservoir of pathogenic microorganisms without any apparent health cost [38,78,79]. The relationship between bacteria infection and body condition could be difficult to untangle because one could argue that individuals in poor body condition would be more prone to infection, however, this is more likely to happen when access to food is reduced and immunity also gets compromised [80,81].…”
Section: Body Conditionmentioning
confidence: 99%
“…It is also considered a farmer friend and is frequently observed in large numbers populating wetlands during irrigation seasons picking up different kinds of soil insects including earthworms, grasshoppers, crickets, crickets, maggots, moths, beetles and others (Issa, 2019; Vega‐Sánchez et al., 2022). On the other hand, cattle egrets can be a safety hazard due to their potential ability to spread pathogens of both human and animal origins (Abd Elfatah et al., 2021; Phalen et al., 2010; Silva et al., 2018), indicating the necessity for further understanding of their functional anatomy, especially that related to the immune system.…”
Section: Introductionmentioning
confidence: 99%